I can see what you mean: Encouraging higher education educators to reflect upon their teaching and learning practice when engaging with blind / vision impaired learners. - Mc Guckin, Conor (My University, 2018)
This article seeks to take the positive learning from the challenges faced by students with disabilities engaged in higher education - in particular those who are blind and vision impaired – and use it to shape practice for educators who seek to engage positively in their pedagogies with these very students and their peers. The article begins by citing some of the factors that have influenced the changes in the student demography within education since the turn of the century. The challenges faced by students with disabilities are well researched and the move from add-on supports to a more inclusive approach is afoot. This however now presents challenges to the professional educator and ‘begs’ the question – ‘Do I, as an educator, need to change my practice?’ Such questioning can realign the focus of education and further prompt us to ask ‘Is the learner the only learner in the education relationship?’ While the result may be more questions than answers – the authors seek to position the learning so that educators ‘will be able to see’ where to position their professional development now and in the future.
PUBLISHED
Keywords: Inclusivity; Professional development; Inclusive Society; BLIND; BLINDNESS; Blindness; Blindness; EDUCATION; VISUALLY IMPAIRED